Biosynthesis of silver nanoparticle from flower extract of Dillenia indica and its efficacy as antibacterial and antioxidant - Gupta A.; Pandey B.C.; Verma J.; Tiwari I.; Sahu A.N.; Manhas R.K.; Kumari N. (My University, 2025)
Dillenia indica is a medicinal tree of the Dilleniaceae and its flower extract was used for the synthesis of silver nanoparticle (AgNPs). The optimal conditions for AgNPs synthesis were as such: 2 mM AgNO3, pH 4.5 and 48-h reaction time. The characteristic band of AgNPs was observed at the wavelength of 435 nm by UV–visible spectroscopic study. Fourier-transform infrared (FTIR) analysis depicted the involvement of several functional groups of plant extracts in the synthesis of AgNPs. Nanoparticles were mostly spherical shaped and uniformly distributed, when observation was made by Transmission electron microscopy (TEM). Energy Dispersive X-Ray (EDX) showed absorption peak approximately at 3 keV thus confirmed the presence of silver metal in AgNP. X-ray diffraction (XRD) investigation and selected area electron diffraction (SAED) patterns showed the crystalline nature of the AgNPs. Dynamic light scattering (DLS) analysis exhibited average size of the nanoparticles as 50.17 nm with a polydispersity index (PDI) value of 0.298. The zeta potential of nanoparticles was observed as −24.9 mV. To assess antibacterial activity, both AgNPs alone or its combination with the antibiotic were tried against six pathogenic bacteria. The combination of AgNPs with antibiotic was maximum effective against Shigella boydii (16.07 ± 0.35) and Klebsiella pneumoniae (15.03 ± 0.20). AgNPs alone showed maximum inhibition for both Gram-positive bacteria: methicillin-resistant Staphylococcus aureus (19.97 ± 0.20 mm) and Enterococcus faecium (19.80 ± 0.15 mm). Maximum inhibition of Enterobactor cloacae and Pseudomonas aeruginosa was observed by antibiotic taken alone. Evaluation through 2,2-diphenyl-1-picrylhydrazyl (DPPH) and DNA nicking assays demonstrated the antioxidant capabilities of the nanoparticles. © 2024 Elsevier Ltd